Pengembangan Sistem Informasi Inventori Berbasis Java Pada CV. Bagaskara Galih Perkasa Jepara - Kusumodestoni, R. Hadapiningradja; Widiastuti, Nur Aeni; Sucipto, Adi; Setiawan, Fendi (JTET (Jurnal Teknik Elektro Terapan), 2018)
CV. Bagaskara Galih Perkasa Jepara is one of the companies engaged in furniture. Current inventory systems still have many shortcomings and weaknesses that cause the companys performance to be less than the maximum. There is inefficient data recording process because the same data recording is done several times because the form is available separately, and the absence of notification "goods are running out" on the current system that causes the delay of decision-making process. The purpose of this study is to develop an inventory information system that can manage data efficiently and facilitates the decision-making process. Object-oriented system development methodology using Rapid Application Development (RAD) method is utilized in this research and it is tested using black box testing and questionnaire. It is developed by system modeling using Unified Modelling Language (UML), Java programming language using Netbeans IDE tools, and MySQL database. Theresult of this research is a computerized inventory information system that can be used efficiently, and features of goods receiving, goods spending, goods inventory report, notice of near-expense supplies, and daily reports. Based on the results of research conducted to measure the feasibility of this product by spreading the questionnaire to thematerialexpert, the rate of user satisfaction is obtained 83.03% and the black box testing conducted by the media expert obtained 93.38%, it can be concluded that the inventory information system is included in the "very eligible" category to use.Keywords :Inventory, Rapid Application Development (RAD), Unified Modeling Language (UML), Java, MySQL, Black box testing